Variations In Interactive Media Development To Improve Mastery Of Arabic Vocabulary/ Variasi Pengembangan Media Interaktif Untuk ‎Peningkatan Penguasaan Kosakata Bahasa Arab - As'ad, Muchamad Kharis; Nadzifah, Izzun; Rosyada, Amrina; Utami, Resgi Widati Tria Lis (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study aims to determine the feasibility of the game